The High School Library : its function in education - Logasa, Hannah (New York : D. Appleton and Company, 1928)
Its chief purpose being to show the function of the library in secondary schools, and to state the underlying educational principles upon which modern high-school library service is based.
North Central association score card for school libraries. -- Magazines suitable for the high school library. -- Selected book lists. -- Selected list of books on school library organization and administration. -- Books on vocations and vocational guidance. -- Library schools.
Includes index.
Keywords: HIGH SCHOOL LIBRARIES